ANALISA PENGARUH REBRANDING TERHADAP BRAND ASSOCIATION DENGAN BRAND IMAGE SEBAGAI VARIABEL INTERVENING TERHADAP CUSTOMER LOYALTY PADA PT TELKOM INDIHOME SURABAYA - Jerry Fransen Thomas (Jurnal Strategi Pemasaran, 2016)
Advances in information technology brings many advantages, especially for the society at large where technology can now be enjoyed by almost all elements of the community without any restrictions and difficulties. In Surabaya, there is one player that targets the upscale community where consumers must understand the view of their consumers mind. This research aims to analyze the impact of Rebranding on Customer Loyalty of IndiHome Surabaya through consideration of Brand Association and Brand Image. This research will be conducted by distributing questionnaries to 150 respendents which are users of IndiHome. Quantitative analysis with path analysis model method were used for techinal analysis.